2019
DOI: 10.1002/jso.25448
|View full text |Cite
|
Sign up to set email alerts
|

High‐level expression of PRSS3 correlates with metastasis and poor prognosis in patients with gastric cancer

Abstract: Background and Objectives Serine protease‐3 (PRSS3) is a known contributor to the genesis and development of malignant tumors, although its role in gastric cancer (GC) is still unclear. Methods PRSS3 expression in GC tissue samples and its relationship with clinicopathological features were analyzed. Effects of GC cellular responses to the introduction of small interfering RNA (siRNA)‐mediated and short hairpin RNA (shRNA)‐mediated interference with tumor PRSS3 expression were also assessed. Results PRSS3 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…It has been widely acknowledged that proteases were aberrantly expressed in several types of cancer cells, which played important roles in metastatic progression. 19 Proteolytic enzymes can degrade cell adhesion molecules and promote epithelial-mesenchymal transition, thus supporting tumor cell motility. 20 In addition, it was reported that proteases can enhance tumor cell invasion through reconstructing the extracellular matrix and they are also essential for metastatic colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely acknowledged that proteases were aberrantly expressed in several types of cancer cells, which played important roles in metastatic progression. 19 Proteolytic enzymes can degrade cell adhesion molecules and promote epithelial-mesenchymal transition, thus supporting tumor cell motility. 20 In addition, it was reported that proteases can enhance tumor cell invasion through reconstructing the extracellular matrix and they are also essential for metastatic colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference was according to the previous procedure with modifications . After seeded into 96 or six‐well plates for overnight, cells were transfected with HN1‐siRNA, c‐Met‐siRNA, or NC‐siRNA (final concentration 50 nM) using lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 2.5 | Cell culture RNA interference was according to the previous procedure with modifications. 13 β-actin was used as an internal control to normalize gene expression, the relative quantification was determined by 2ΔCt method.…”
Section: Kaplan-meier Plottermentioning
confidence: 99%
“…The PRSS3 (serine protease 3) gene product, trypsin-3, is a trypsinogen of the trypsin family of serine proteases and is expressed in multiple organs, such as the lung. The PRSS3 gene is located on the locus of T-cell receptor beta variable orphan on chromosome 9 ‘[cytogenetic location: 9p13.3; genomic coordinates (GRCh37/hg19) 33750677-33799229] and is associated with thyroiditis and Rickettsialpox ( 37 , 38 ). This gene is localized to the locus of T-cell receptor beta variable orphans.…”
Section: Discussionmentioning
confidence: 99%